The effect of repeated freezing and thawing of serum on the activity of antibodies - Cecchini, G.; Tekelye Bekele; Kasali, O.B. (Springer, 1992)
Describes experiments in which the effect of repeated freezing and thawing on the stability and activity of bovine antibodies has been studied using the enzyme linked immunosorbent assay (ELISA) against the infectious bovine rhinotrachietis/infections pustular vulvovaginitis (IBR/IPV); and using the Rose Bengale test (RBT) and the serum agglutination test (SAT) to detect the presence of antibodies against bovine brucellosis.